Peluang, Tantangan Dan Strategi Pengembangan Pariwisata Syariah Berbasis Ekonomi Komunitas Untuk Meningkatkan Daya Tarik Wisatawan - Faridatun Najiyah; Noor Iffatin Nadhifah (Journal of Islamic Economics and Finance, 2023)
This research has the purpose of finding out that tourism development can also be said to be a process in order to improve and improve something that already exists. Tourism development can be in the form of development, maintenance and preservation of plants, infrastructure and other facilities. Three main principles in sustainability development: 1) Ecological Sustainability, which is to ensure that the development carried out is in accordance with the existing ecological, biological, and diverse ecological processes. 2) Social and Cultural Sustainability, which is to ensure that the development carried out has a positive impact on the life of the surrounding community and is in accordance with the culture and values that apply to the community. 3) Economic Sustainability, which is to ensure that the development carried out is economically efficient and that the resources used can survive for future needs.